2018
DOI: 10.1186/s12884-018-1917-8
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent childbearing trends and sub-national variations in Ethiopia: a pooled analysis of data from six surveys

Abstract: BackgroundEthiopia houses the second largest population of female adolescents in Africa. Adolescent childbearing can have detrimental effect to the health and wellbeing of women and their offspring. This study examined trends, sub-national variations and determinants of early childbearing (i.e. childbearing before age 20) in Ethiopia.MethodsData from the 2000–2011 Ethiopia Demographic and Health Surveys and from the 2014–2016 Performance Monitoring and Accountability surveys were pooled for this analysis. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 12 publications
(12 reference statements)
11
16
0
Order By: Relevance
“…The possible justi cation of a high proportion of early marriage in Amahara, Afar, and Gambela region might be deep-rooted traditions such as, considering marriage as a success for the girl and her family, ensuring the virginity of the girl when she marries, the concern that the girl will become too old for marriage, and creating a bond with the bridegroom's family (13) This study evidenced that, as the age of mothers increases the likelihood to have an early marriage decreases. This nding is consistent with studies conducted in Ethiopia (28,29). The possible justi cation might be with young women who had married at ages <20, those married before age 20 were less likely to have known about the disadvantage of early marriage because of teenage (30).…”
Section: Discussionsupporting
confidence: 90%
“…The possible justi cation of a high proportion of early marriage in Amahara, Afar, and Gambela region might be deep-rooted traditions such as, considering marriage as a success for the girl and her family, ensuring the virginity of the girl when she marries, the concern that the girl will become too old for marriage, and creating a bond with the bridegroom's family (13) This study evidenced that, as the age of mothers increases the likelihood to have an early marriage decreases. This nding is consistent with studies conducted in Ethiopia (28,29). The possible justi cation might be with young women who had married at ages <20, those married before age 20 were less likely to have known about the disadvantage of early marriage because of teenage (30).…”
Section: Discussionsupporting
confidence: 90%
“…Regarding region of residence Oromia, SNNP, Eastern pastoralist and western semi-pastoralist regions significantly increased the hazard of first birth at an early age compared to most urban regions (Addis Ababa, Dire Dawa, and Harare), controlling for other factors and holding cluster effect the same. This finding was coherent with the study reported in Ethiopia (60) and Ghana (31).This might be due to fewer proportions of educated women, and access to contraceptive and reproductive health issues in rural regions (28). Furthermore, women in rural regions might have less decision making role regarding their reproductive health and timing of first birth.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the studies revealed that having poor and middle wealth index status was identified as the risk of age at first birth in early age (24,(30)(31)(32)(35)(36)(37)41,44). (5,6,(33)(34)(35)(36)(37)(38)9,14,17,20,21,25,30,31). The majority works of the literature revealed that the use of any contraception delay age at first birth (5,8,9,20,30,31,34,39,40) On the other hand, advanced maternal age (> 30 years) at first birth is associated with an increased risk of fetal loss, chromosomal anomalies, multiple pregnancies, hypertension, diabetes mellitus, preterm birth, low birth weight, breast cancer and maternal mortality (16,22,23).…”
Section: Introductionmentioning
confidence: 99%
“…The possible justi cation of a high proportion of early marriage in Amahara, Afar and Gambela region might be deep-rooted traditions such as, considering marriage as a success for the girl and her family, ensuring virginity of the girl when she marries, the concern that the girl will become too old for marriage, and creating a bond with the bridegroom's family (13) This study evidenced that, as the age of mothers increases the likelihood to have an early marriage decreases. This nding is consistent with studies conducted in Ethiopia (27,28). The possible justi cation might be with young women who had married at ages <20, those married before age 20 were less likely to have known about the disadvantage of early marriage because of teenage (29).…”
Section: Discussionsupporting
confidence: 90%